A new species of Nemophora from Korea (Lepidoptera, Adelidae, Adelinae) - Ko, Jae-Ho; Yagi, Sadahisa; Hirowatari, Toshiya (Zootaxa, 2023)
A new species of the genus Nemophora Hoffmannsegg, Nemophora lutea Ko & Hirowatari sp. nov. is described from Korea, which is very similar to N. smaragdaspis (Meyrick) found in India and Nepal but distinguished by its the straight deep orange median band and metallic white lines on the forewing in both sexes. Illustrations of adults and genitalia are provided, with habitat information.